IMMUNOPATHOLOGICAL STUDY OF FASCIOLA HEPATICA AND HYDATID FLUID ANTIGENS ON HYDATID CYSTS DEVELOPMENT IN MICE (Iraqi Journal of Medical Sciences, 2016)
Background: Hydatidosis is a chronic cyst forming helminthic disease of human, domestic and wild animals. The immune responses play a pivotal role in limiting cystic larval development.Objective:To investigate the immunopathological effects of Fasciola hepatica antigens (FHAgs) and hydatid cyst fluid antigens (HCFAgs) on the immune response against hydatidosis in mice.Methods: One hundred mice were divided into 5 groups; the 1st three were immunized subcutaneously with 0.2 ml of HCFAgs, FHAgs and mixed antigen (MAg = HCFAgs+FHAgs), respectively. The last two regarded as control groups. On day 27 post immunization, the skin test was done for the 1st four groups. On day 30, half the animals of each group were scarified to perform E-rosette test, agar gel diffusion (AGD), and ELISA test. The rest of the mice with the 5th group were challenged with 2000 viable protoscolex / mouse. After 3 months, they were scarified for gross and histopathological examination.Results:The immunized group with MAg was hypersensitive prior to challenge the skin test, while E-rosette test indicated the highest ratio of active lymphocytes before and after challenge in comparison with other groups. The AGD test showed severe reaction between the sera of mice immunized with MAg against the FHAgs against HCFAg and between sera of immunized group with FHAgs against HCFAg and vice versa. The highest level of antibodies was recorded in the immunized group with MAg. Histopathological examination for the internal organs of immunized groups revealed granulomatous lesions, reduction in the number of cysts with lymphocytic hyperplasia and presence of degenerative protoscolices. Control infected group revealed growth of cysts in the internal organs, with degenerative and necrotic lesions.Conclusion:The 3 types of Ags stimulate humoral and cellular immunity was proved by immune-histopathological investigations. The MAg was highly immunogenic in comparison with each Ag alone. This antigenic activity may be due to the presence of synergistic interactions and cross-reactivity between the 2 parasites and this can be used as protective value against hydatidosis in the intermediate hosts.Keywords :Parasitic infections, immunological cross reaction, isolation parasitic antigens, Fasciola hepatica antigens, Hydatid fluid antigens.
Keywords: Parasitic infections; immunological cross reaction; isolation parasitic antigens; Fasciola hepatica antigens; Hydatid fluid antigens